2022
DOI: 10.1155/2022/4621446
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Community Health Worker-Led Intervention on Knowledge, Perception, and Prostate Cancer Screening among Men in Rural Kenya

Abstract: Background. Globally, an increase in mortality from prostate cancer (PC) remains a big challenge with disparities existing with a slight preponderance among men in low and middle-income countries. Prostate cancer is a leading cause of mortality among men in sub-Saharan Africa. In Kenya, despite the majority of men presenting with advanced prostate cancer for treatment, knowledge and screening for prostate cancer is low. The study aimed to examine the effectiveness of a community health worker-led education int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Such trials can use the alleviation of symptoms and the reduction of PSA as endpoints in relatively small and short randomized studies; these are needed to make progress in providing medical care for men with prostate cancer in SSA and other LLMICs around the world. Additionally needed is: the training of more urologist and urologic oncologists, focusing on their ability to perform biopsies and prostate surgery; the improvement of clinical facilities, including those for radiotherapy and laboratory and pathology diagnosis; the development of prostate cancer awareness and education among the general public, as well as the medical community in SSA [42].…”
Section: Discussionmentioning
confidence: 99%
“…Such trials can use the alleviation of symptoms and the reduction of PSA as endpoints in relatively small and short randomized studies; these are needed to make progress in providing medical care for men with prostate cancer in SSA and other LLMICs around the world. Additionally needed is: the training of more urologist and urologic oncologists, focusing on their ability to perform biopsies and prostate surgery; the improvement of clinical facilities, including those for radiotherapy and laboratory and pathology diagnosis; the development of prostate cancer awareness and education among the general public, as well as the medical community in SSA [42].…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring this subject are, however, scarce in our study setting. Foreign studies 28,29 have shown the roles of nurses and community healthcare workers in health promotion and SDM relating to PCa screening. These roles should be encouraged among these nonmedical PHC cadres, who are first-line PHC providers in South African local communities and clinics.…”
Section: Introductionmentioning
confidence: 99%